(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1991)
The construction of the Monte Olimpino 2 railway tunnel connecting Chiasso (Switzerland) and Bernate (to the South of Como, Italy) allowed the continuous observation of the poorly outcropping Mesozoic to Cenozoic succession and the collection of new stratigraphic and structural data which are significant for the reconstruction of the South-alpine margin evolution. The Mesozoic succession (lower Jurassic to lower Cretaceous) is strongly tectonized and thinned. The Selcifero Lombardo is represented by a sliver of radiolarites; the Maiolica is only 15 m thick and the Scaglia Variegata reaches a maximum local thickness of 1.5 m of cataclastic marls. From a stratigraphic point of view the presence of lithofacies referable to the lower lithozone of the Sogno Formation (upper Lias) is noteworthy. They occurr at the same stratigraphic position of the nearly outcropping Rosso Ammonitico Lombardo (Breggia river, Switzerland) and are indicative of relatively deeper sedimentation within the Generoso Basin. The overlying Oligocene to middle Miocene deep marine clastic succession, the "Gonfolíte Lombarda", is separated from the Mesozoic succession by a North-vergent thrust. Four depositional sequences have been recognized on the basis of major unconformities and of the progradation-retrogradation pattern of the depositional system. A gradual increase of the tectonic tilt from the bottom to the top ("progressive unconformity"), recurrent cannibalization phenomena and lateral shifting of the clastic buildups characterize the whole succession.